Antibiofilm activity of probiotic bacteria Lactobacillus plantarum FNCC 0020 against Streptococcus mutans serotype c - Pribadi, Nirawati; Sampoerno, Galih; Juniarti, Devi Eka; Goenharto, Setyabudi; Zubaidah, Nanik; Ramadhini Arrianti, Tyas; Ramadhani, Aqila Shabrina Dwi; Fadhillah, Revita Rizki (Conservative Dentistry Journal, 2025)
Background: Streptococcus mutans (S. mutans) is a Gram-positive bacterium that plays a role in dental caries. Plaque and biofilm formation can be chemically cleaned using mouthwash, such as chlorhexidine gluconates (CHX) 0.2%, which is the gold standard. Another alternative can be developed to inhibit S. mutans biofilm formation by using Lactobacillus plantarum probiotic, which has antibiofilm potency by producing antimicrobial substances. Purpose: This study tested the biofilm inhibition to determine the Inhibitory Concentration that can inhibit 50% of biofilm formation. Methods: This research was conducted as an in vitro experimental laboratory study. Biofilm inhibition testing was performed by using the microdilution method on biofilms formed in 96 well microplates with 0,1% crystal violet staining. Lactobacillus plantarum FNCC 0020 was diluted to several concentrations: 12.5%, 25%, and 50% against Streptococcus mutans biofilm induced by 3% sucrose. The test results in optical density were read using a spectrophotometry with a wavelength of 650 nm. were determined using the GraphPad Prism sigmoidal dose-response method. Results: There is antibiofilm activity of Lactobacillus plantarum FNCC 0020 against Streptococcus mutans, and the inhibitory effect against Streptococcus mutans biofilm showed of 42.43%. Conclusion: Lactobacillus plantarum FNCC 0020 at 50% has biofilm inhibitory activity compared to other concentrations but is less effective than 0.2% CHX.